Screening and evaluation of potential bacteria isolated from gut microflora of channa sp. (Haruan) / Mohd Azlan Mohd Asari - Mohd Asari, Mohd Azlan (Faculty of Applied Sciences, 2014)
A study has being conducted on the Channa sp. obtained from pond of UiTM Kuala Pilah, Negeri Sembilan. The study aim is to isolate the potential bacteria from gut microflora of Channa sp. which can be used in aquaculture and human health. A total of 94 bacteria were successfully isolated from 2 samples of Channa sp. obtained from pond site A. All the isolated bacteria were screening for it antagonism activity by using preliminary cross streak test against pathogenic bacteria Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa. Out of 94 bacteria isolated, only 7 isolated bacteria A1, A6, A23, A30, A37, B14 and B49 showed antagonism activity against pathogenic bacteria tested. Then were further tested for it haemolytic activity and gram stain. Only bacteria A6 that show Gamma haemolysis and Gram positive were choosed for confirmation its antagonism activity ability using agar well diffusion test and identification of colony morphology. This study show that only bacteria A6 might become the potential bacteria that can be used in the future isolated from the gut microflora of Channa sp. obtained from pond in UiTM Kuala Pilah, Negeri Sembilan.